Domestic and International Causes of Russian Military Intervention in Ukraine - Romańczuk, Michał (Historia i Polityka, 2021)
The collapse of the Cold War order led to a change in the geopolitical environment of the Russian Federation. The declarations of independence of the former Soviet republics and the emergence of the post-Soviet area had weakened the country’s position. As a result, the Russian Federation has been perceiving this new area as a zone of its ‘vital interests’, and attaining and maintaining dominant position in those territories has been considered crucial for the state’s security, its strength and position on the international arena. Russia has been pursuing its goals in the area through numerous reintegration attempts on political, military and economic levels. To achieve the main political goal, which is the control over the post-Soviet area, the Russian Federation has been also using military instruments. The focal point and purpose of this article is to show the internal and external causes of military intervention of the Russian Federation in eastern Ukraine.